2009
DOI: 10.1073/pnas.0900977106
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal M 3 muscarinic acetylcholine receptors are essential for somatotroph proliferation and normal somatic growth

Abstract: The molecular pathways that promote the proliferation and maintenance of pituitary somatotrophs and other cell types of the anterior pituitary gland are not well understood at present. However, such knowledge is likely to lead to the development of novel drugs useful for the treatment of various human growth disorders. Although muscarinic cholinergic pathways have been implicated in regulating somatotroph function, the physiological relevance of this effect and the localization and nature of the receptor subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…The M3R, a prototypic class A GPCR that preferentially couples to G proteins of the G q family, is involved in numerous important physiological functions (34 -36). For example, recent studies with M3R mutant mice have shown that M3Rs expressed by pancreatic ␤ cells play a key role in maintaining normal blood glucose levels (37) and that neuronal M3Rs are required for proper somatic growth (38) and bone formation (39). Moreover, Raufman et al (40) recently demonstrated that enhanced M3R activity may play a role in the pathogenesis of colon cancer.…”
mentioning
confidence: 99%
“…The M3R, a prototypic class A GPCR that preferentially couples to G proteins of the G q family, is involved in numerous important physiological functions (34 -36). For example, recent studies with M3R mutant mice have shown that M3Rs expressed by pancreatic ␤ cells play a key role in maintaining normal blood glucose levels (37) and that neuronal M3Rs are required for proper somatic growth (38) and bone formation (39). Moreover, Raufman et al (40) recently demonstrated that enhanced M3R activity may play a role in the pathogenesis of colon cancer.…”
mentioning
confidence: 99%
“…These observations suggest that central M 3 receptors do not play a significant role in regulating these processes. Interestingly, however, the brain-M3-KO mice displayed a dwarf-like appearance (adult mutant mice were~10% shorter than control littermates; Gautam et al 2009). This phenotype was associated with a significant reduction in the serum levels of growth hormone (GH) and insulin-like growth factor I (IGF-1; Fig.…”
Section: Neuronal M Machrs Are Critical For the Proper Development Ofmentioning
confidence: 99%
“…To shed light onto the roles of central M 3 mAChRs, Gautam et al (2009) used Cre/loxP technology to generate mutant mice that lacked M 3 receptors specifically in neurons and glial cells (brain-M3-KO or Br-M3-KO mice). These mice were obtained by crossing a Cre transgene driven by the nestin promoter into mice that were homozygous for a floxed version of the M 3 receptor gene.…”
Section: Neuronal M Machrs Are Critical For the Proper Development Ofmentioning
confidence: 99%
See 2 more Smart Citations